Analysis of Student Acceptance of SPADA E-Learning Using UTAUT Method - Syekh Budi Syam; Muh. Jamil; Aldi Bastiatul Fawait (SEULANGA SYSTEM PUBLISHER, 2024)
SPADA UWGM is an e-learning platform used by Widyagama Mahakam University Samarinda (UWGM). This platform has been used since 2020 for the teaching and learning process, both to provide materials, assignments, and quizzes and to take attendance. The use of e-learning is certainly a technological innovation in the field of education. This progress is something that cannot be avoided because it is also strongly supported by the advancement of science, so there needs to be a measurement of the extent to which this e-learning can be accepted from the perception of its users. This study uses the UTAUT method with six variables, namely performance expectancy, effort expectancy, social influence, facilitating condition, use behavior, and Behavioral Intention to measure the level of student acceptance of SPADA UWGM. The questionnaire used was a questionnaire with answer choices in the form of a Likert scale and was processed using the smart PLS application to see the reliability and validity of the questionnaire items and prove the hypothesis between variables with an error tolerance limit of 10%. The results of this study indicate that performance expectancy does not affect behavior intention. While effort expectancy and social influence influence behavior intention. Other things such as facilitation conditions and behavioral intentions influence use behavior. So based on the research conducted, it can be concluded that the performance of the SPADA UWGM e-learning system does not influence students' interest in using and utilizing the existing e-learning system. Meanwhile, social influence and a sense of trust that the existing system is easy to use have a significant influence on students' efforts and intentions in using the SPADA UWGM e-learning system. Other things such as the condition of campus facilities in supporting the use of the system have an influence on students' seriousness in using the e-learning system, which means that the better the facilities, the more students' motivation will increase in utilizing SPADA UWGM sustainably.